Life Cycle Impact Assessment (LCIA) of potable water production in Malaysia: A comparison among different technology used in water treatment plant - Sharaai, A.H.; Mahmood, N.Z.; Sulaiman, A.H. (2010)
LCA is a systematic procedure which assesses the lifecycle of a product to analyze the extent of its environmental impact contribution. In this LCA study comparison between three different water treatment plants in Malaysia have been conducted. Conventional Plant (using Dissolved Air Floatation (DAF) and Pulsatube Â® Clarifier Technology) must undergo treatment process uses a standard system of screening, coagulation and flocculation, sedimentation, filtration and disinfection processes. While nonconventional plant using Ultrafiltration (UF) not does go through processes like conventional plant. In reviewing the water treatment process by using LCA procedures, detailed information of every process involved is needed, including acquiring the energy information and materials consumed during the entire treatment process. The LCA procedure applied in this research uses the ISO 14040 series. Data inventory from selected month will be analyzed to gauge the impact to the environment using Eco-indicator 99 method. The high consumption of electricity in UF and DAF technologies is the contributing factors to the depletion of natural resources. Even though the electricity consumption in pulsatube Â® clarifier technology is seen as efficient, but its PAC chemical usage is seen as the major contributor to the reduction of environmental quality and human health.